COPING STRATEGY AND CHILDREN CHARACTERISTIC TO PARENTAL ACCEPTANCE IN PARENTS OF CHILDREN WITH LEUKEMIA USING TRANSACTIONAL THEORY APPROACH - Iqlima Dwi Kurnia; Yuni Sufyanti Arief; Kristiawati Kristiawati (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2015)
Introduction. Leukemia is a kind of cancer that most occur in children 33% of the total number of childhood cancer. The purpose of this study was to determine the relationship of coping strategy and children characteristic to parental acceptance in parents of children with leukemia.Method. Design used in this study was cross-sectional. Population in this study was parents (mothers) of children with leukemia in Dr. Soetomo Hospitals Surabaya, with consecutive sampling technique. Total sample was 23 mothers. Coping strategy measurement was done using questionnaire modification from Lazarus & Folkman Appraisal stress and coping strategy in Transactional Theory, parental acceptance was measured using questionnaire. Data that obtained then was processed and analyzed using spearman and pearson correlation, alternative hypothesis would be accepted if p<0,05.Result. The results of this study showed that the relationship between coping strategy with parental acceptance was significant (p = 0.000). For the relationship between children characteristics with parental acceptance, variable of phase of treatment, illness classification and duration of illness showed a significant result (p = 0.000), whereas variables of children age and children sequences showed insignificant results with parental acceptance.Discussion. Good parental acceptance will only happen if parents are willing and capable in understanding themselves.Keywords: Parental acceptance, children leukemia, primary appraisal, coping strategy